Variation and association of wood properties of South African grown Eucalyptus grandis (Hill ex Maiden) clones - Retief, R. J.(Rachel Johanna) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.